Conservation and innovation - the evolution of the metazoan microRNA landscape and its contribution to reproduction and development - Quah, S (2015)
There are major gaps in our understanding of the evolution of microRNA (miRNA) genes and how this relates to evolutionary changes in metazoan development. miRNAs function as trans-acting post-transcriptional modulators of gene expression. They are implicated in the canalization of development and the consequent provision of evolvability. Here I present data and analyses on miRNA evolution in insects and mammals, both on a phylogenetic scale as well as at the level of individual miRNA genes. I also perform case studies cross-comparing the expression and functions of intronic miRNAs to those of their host genes, and compare tissue-specific enrichment of miRNAs in a specific tissue (butterfly ovary) relative to the whole body. A broad overview of miRNA evolution across a clade is presented for the Lepidoptera using a combination of small RNA sequencing in two lepidopteran species coupled with bioinformatic analysis of available genomic and miRNA data across the clade. This analysis reveals a burst of rapid miRNA gain on the stem lineage of the Lepidoptera prior to the radiation of the diverse butterfly and moth lineages. I also propose that the uneven distribution of miRNA gain across the lepidopteran phylogeny, coupled with observations of high numbers of newly-emergent miRNAs on terminal branches, is evidence for a model of miRNA evolution comprising high rates of turnover for newly-acquired miRNAs with variable rates of stable miRNA retention. In depth examination is carried out on two miRNA genes, both of which occur within homeobox gene introns - eutherian-specific mir-615 and lepidopteran-specific mir-2768. Phylogenetic distribution and theories for the acquisition of mir-615 in Eutheria are considered. A combination of publicly available expression data and epigenetic modification data is used to demonstrate the existence of transcriptional regulation for mir-615 independent from that of its host gene. The study of mir-2768 reveals the first experimental evidence for an intronic miRNA performing a complementary function to that of its host gene. I also present the first miRNA transcriptome from a butterfly ovary and compare this to whole-body miRNA expression in the same species. This provides insights into the roles performed by miRNAs in the butterfly ovary, including conserved functions, and enables comparison of ovarian miRNA tissue specificity relative to time of origin. Overall, this work provides a multi-faceted analysis of miRNA evolution in animals and presents an integrated approach to our understanding of the roles of miRNAs in evo-devo.